Strategi Public Relations dalam Pengembangan Brand Image Sekolah di Sekolah Dasar Islam Terpadu (SDIT) Kota Samarinda - Ida Suryani Wijaya; M. Al Amin (Lentera: Jurnal Ilmu Dakwah dan Komunikasi, 2020)
Public relation is an important aspect within the process of building positive image for an organization. Selecting appropriate strategy, therefore, must be applied very carefully since it determines the success or failure of the organization in the long run. This paper, thus, aims at explaining the strategy of public relation applied by Cordova Integral Islamic Elementary School in Samarinda in building a positive brand image that suits its’ long-term objectives. Utilizing qualitative approach, this paper finds out that Cordova Integral Islamic Elementary School in Samarinda applies four strategy such as research-listening, planning-decision, communication-action, and evaluation.Keywords: Image brand, organizational strategy, and public relation.